Brain‐derived neurotrophic factor inhibits neuromuscular junction maturation mediated by inTracellular Ca2+ and Ca2+/calmodulin‐dependent kinase. Issue 4 (April 2016) - Song, Wei; Jin, Xiwan Albert
ABSTRACT: Introduction: Brain‐derived neurotrophic factor (BDNF) inhibits neuromuscular junction (NMJ) maturation. In this study we investigated the underlying molecular mechanisms of this process. Methods: We used a patch‐clamp technique to measure spontaneous synaptic currents (SSCs) from innervated muscle cells in Xenopus nerve–muscle cocultures. Results: In the presence of Ca 2+ /calmodulin‐dependent kinase (CaMK) inhibitor KN93, SSC amplitude (226.3 ± 26.5 pA), frequency (30.9 ± 10.1 events/min), and percentage of bell‐shaped amplitude distributions (47.1%) were reversed to control levels (286.7 ± 48.2 pA, 26.2 ± 5.8 events/min, and 47.1%, respectively). Depletion of intracellular Ca 2+ by BAPTA‐AM or thapsigargin had similar reversal effects to KN93. In addition, cotreatment with both 2‐APB (IP3 receptor inhibitor) and TMB‐8 (ryanodine receptor inhibitor) also reversed the inhibitory effects of BDNF, as shown by the physiological parameters. Conclusions: CaMK mediates the inhibitory effects of BDNF on NMJ maturation. Ca 2+ released from intracellular stores through either IP3 receptors or ryanodine receptors regulates neurotrophic actions on NMJ maturation. Muscle Nerve 53 : 593–597, 2016